The Influence of Organizational Restructuring, Organizational Culture and Organizational Commitment on Employee Performance at Perum LKBN ANTARA - Hamsinah Hamsinah (Universitas Negeri Makassar, 2021)
This study aims to determine the exact and clear empirical picture of the phenomena that exist in Perum LKBN ANTARA and the policies perceived by employees in increasing management professionalism. This study uses a quantitative approach with a survey in order to collect data whose analysis results will be presented in the form of numbers. the results of significant multiple linear regression analysis with a calculated F value of 62.407 with a significance level of 0.000. The significance value is still below the set significance value of 0.05 and positive, so it can be concluded that restructuring, organizational culture and organizational commitment have a significant effect on employee performance at LKBN Antara. The better the restructuring, organizational culture and organizational commitment of Perum LKBN ANTARA, the higher the performance of LKBN Antara's employees. Vice versa, if the restructuring, organizational culture and organizational commitment of Perum LKBN ANTARA are not good, then the performance of LKBN Antara employees will decrease.